Seismotectonic implications of the South Chile ridge subduction beneath the Patagonian Andes - Suárez, Rodrigo Javier; Sue, Christian; Ghiglione, Matias; Guillaume, Benjamin; Ramos, Miguel Esteban; Martinod, Joseph; Barberon, Vanesa (Terra Nova)
The South Chile ridge (SCR) intersects the Patagonian trench around 46°09′S, forming the triple junction among the Antarctic, Nazca, and South America plates. Subduction of the SCR since ~18 Ma produced the opening of a slab window beneath Patagonia and a noticeable magmatic gap in the cordillera, profuse volcanism and topographic uplift in the retroarc. To study seismicity distribution and present-day stress resulting from this particular framework, we analyse databases of seismic events and earthquake focal mechanisms. Our study finds that clusters of intraplate crustal seismic events are disrupted by a ~450–470 km seismicity gap above the slab window. Calculated stress tensors depict a strike-slip tectonic regime north of the triple junction, and ~W-E compression to the south of the seismic gap. We propose that the seismotectonic behaviour of the upper plate is disturbed at the first order by the trench-ridge intersection, leading to a heterogeneous stress field. Fil: Suárez, Rodrigo Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Sue, Christian. Universite de Franche-Comte; Francia Fil: Ghiglione, Matias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Guillaume, Benjamin. Universite de Rennes I; Francia Fil: Ramos, Miguel Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. ...